Simultaneous Infrared Spectroscopy, Raman Spectroscopy, and Luminescence Sensing: A Multispectroscopic Analytical Platform - Klingler, Sarah; Hniopek, Julian; Stach, Robert; Schmitt, Michael; Popp, Jürgen; Mizaikoff, Boris (ACS Measurement Science Au, 2022)
Scientific questions in fields such as catalysis, monitoring of biological processes, or environmental chemistry demand analytical technologies combining orthogonal spectroscopies. Combined spectroscopic concepts facilitate in situ online monitoring of dynamic processes providing a better understanding of the involved reaction pathways. In the present study, a low-liquid-volume multispectroscopic platform was developed based on infrared attenuated total reflection (IR-ATR) spectroscopy combined with Raman spectroscopy and luminescence sensing. To demonstrate the measurement capabilities, exemplary analyte systems including water/heavy water and aqueous solutions of ammonium sulfate were analyzed as proof-of-principle studies. It was successfully demonstrated that three optical techniques may be integrated into a single analytical platform without interference providing synchronized and complementary data sets by probing the same minute sample volume. In addition, the developed assembly provides a gastight lid sealing the headspace above the probed liquid for monitoring the concentration of molecular oxygen also in the gas phase via luminescence quenching. Hence, the entire assembly may be operated at inert conditions, as required, for example, during the analysis of photocatalytic processes.
CRIS-Team Scopus Importer:2023-04-20
Keywords: ammonium sulfate; ATR; attenuated total reflection; combined spectroscopic methods; D; H; infrared spectroscopy; luminescence quenching; luminescence sensing; multispectroscopic platform; oxygen; Raman spectroscopy